1,001 sermon illustrations and quotations - Geikie, Cunningham, 1824-1906 ed (Minister's handbook series., 1952)
This particular book goes beyond the usual books of sermon illustrations. It gives numerous quotations from scripture, which are also suggestive as texts for sermons on problems facing the world and the individual Christians today. The many terse quotations will often be found to be just the thing needed to enliven and give point to the sermon. The hundreds of anecdotes were carefully selected for their value in illuminating their respective subjects.